Analisis Manfaat Investasi Teknologi Informasi Nirmala Hadir pada Koperasi Nirmala - Luh Ketut Kartika Candra Dewi; I Gusti Agung Pramesti Dwi Putri; Linda Yupita (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
The rapid development of Information Technology (IT) is currently creating new habits and facilitating life activities from all aspects which is a challenge for various parties, including non-bank financial companies, to be prepared to face business competition through the application of information technology. One of the companies investing in information technology is the Nirmala Cooperative by presenting Nirmala Hadir e-commerce to support its business units and prioritize convenience for its members. When developing digital technology, companies need a large capital investment with an uncertain percentage of return and the measurement is quite difficult to do so an analysis of the benefits of technology investment is needed to ensure that the benefits obtained are higher than the negative impacts that arise. The method applied in this research is a qualitative descriptive approach which in its analysis uses the Ranti's Generic IS/IT Business Value and Cost Benefit Analysis (CBA) methods. The results of research with Ranti's Generic IS/IT obtained 7 categories and 9 sub-categories of benefits and CBA calculations obtained an ROI value of 7.93%, NPV of IDR 11,731,529, Payback Period of 0.929 (339 days) and BCR of 9.87 which indicates that the technology investment made by the Nirmala Cooperative has a good profitability value with a payback period of less than one year.